ZOOMORPHIC IMAGES IN METAPHORICAL THINKING - Ulugova Shokhida Shokhrukhovna; Axtamova Ruxshona Murodovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract. This article is devoted to the role and use of metaphors,or zoo metaphors,which are of great importance not only in linguistics,but also in fiction literature. Also, the article describes the characteristics of a metaphor, a narrow range of metaphors, and basic metaphors.Through the information provided below, we will clarify the reasons for the use of animal metaphors in fiction and in the works of poets and writers.